Less invasive and equivalent short‐term outcomes with simultaneous en bloc robot‐assisted radical cystectomy and laparoscopic nephroureterectomy: Comparison with conventional open radical cystectomy and nephroureterectomy. Issue 2 (3rd October 2021) - Kamei, Jun; Fujisaki, Akira; Saito, Kimitoshi; Sugihara, Toru; Ando, Satoshi; Miyagawa, Tomoaki; Takayama, Tatsuya; Fujimura, Tetsuya
Abstract: Introduction: To clarify the safety and efficacy of en bloc simultaneous robot‐assisted radical cystectomy (RARC) and laparoscopic nephroureterectomy (LNU) for synchronous muscle‐invasive bladder carcinoma and upper tract urothelial carcinoma (UTUC) or UTUC of a solitary kidney, we evaluated the perioperative and short‐term outcomes of this surgical procedure compared with those of simultaneous open radical cystectomy and nephroureterectomy. Methods: We prospectively enrolled consecutive patients receiving en bloc simultaneous RARC and LNU between December 2018 and March 2020 at two institutes. Patients' characteristics, surgical, perioperative, and pathological outcomes and recurrence rate within 6 months were compared with a historical control receiving simultaneous open radical cystectomy and nephroureterectomy. Results: Ten patients receiving simultaneous RARC and LNU and 17 receiving simultaneous open radical cystectomy and nephroureterectomy were included in the study. Simultaneous RARC and LNU significantly reduced bleeding volume and blood transfusion ( P < .0001, P < .0001, respectively) and significantly prolonged operating time ( P = .035). RARC and LNU significantly shortened hospitalization after operation ( P = .003) and showed reduced tendency of postoperative complications within 30 days but not significantly ( P = .25). Pathological characteristics and recurrence within 6 months were not significantly different between the two groups. Conclusion: Our results suggested that en bloc simultaneous RARC and LNU were safer surgical procedures with equivalent short‐term oncological outcomes compared to conventional open procedures. It can be a standard minimally invasive surgical method in countries where robot‐assisted radical nephroureterectomy is inaccessible.